Оптимізація змісту підготовки до бізнес-планування майбутніх інженерів-педагогів економічного профілю - Кошелєва, В. С. (НТУ "ХПІ", 2010)
В статье представлены результаты оптимизации содержания подготовки к бизнес-планированию будущих инженеров-педагогов экономического профиля. Оптимизация предполагает выделение в структуре бизнес-плана его базового инварианта и вариативных частей.

In the article the results of optimization of maintenance of preparation to business-planning of future engineers-teachers of economic type are represented. Optimization supposes the selection in the structure of business plan of his base invariants and variety parts.
Оptimization of maintenance of preparation to business-planning of future engineers-teachers of economic type
Keywords: економіка України; управління підприємством; ринок інтелектуальної власності; викладачі; фінансова звітність; формування знань